2016
DOI: 10.1002/ejp.957
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of systemically administered dipyrone (metamizol), magnesium chloride or both in a murine model of cancer

Abstract: This study shows a non-opioid analgesic combined with an adjuvant as a therapeutic option to treat cancer pain. The avoidance of antinociceptive tolerance when repeated administration is required, as well as tumor growth reduction, are additional advantages to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…They also reported that at higher doses, metamizole was as effective as morphine 60 mg/day [58,60]. Metamizole in combination with magnesium chloride was shown to reduce cancer pain while also preventing tolerance in a study conducted with murine model of cancer [61]. Hearn and colleagues detailed in their systematic review, from eight studies, 70% of the adult patients with acute postoperative pain who were treated with a single dose of metamizole experienced at least 50% of maximum pain relief over 4–6 h [59].…”
Section: Pain Medication Opioid Analgesics and Non-steroidal Antimentioning
confidence: 99%
“…They also reported that at higher doses, metamizole was as effective as morphine 60 mg/day [58,60]. Metamizole in combination with magnesium chloride was shown to reduce cancer pain while also preventing tolerance in a study conducted with murine model of cancer [61]. Hearn and colleagues detailed in their systematic review, from eight studies, 70% of the adult patients with acute postoperative pain who were treated with a single dose of metamizole experienced at least 50% of maximum pain relief over 4–6 h [59].…”
Section: Pain Medication Opioid Analgesics and Non-steroidal Antimentioning
confidence: 99%
“…33 and combined with medetomidine + midazolam by Kawai et al. 34 As shown in other species 35,36 and in mice, 37,38 metamizole is a potent analgesic and can reduce the required dose of other anaesthetics when administered in combination. The doses of butorphanol and metamizole were chosen in accordance with Erhardt et al.…”
Section: Discussionmentioning
confidence: 98%
“…Depending on the painful stimulus of the experiment, more potent analgesics could be necessary. Butorphanol, an opiate agonist-antagonist, 7 was recommended for use combined with dexmedetomidine þ tiletamine þ zolazepam in mice by Cagle et al 33 and combined with medetomidine þ midazolam by Kawai et al 34 As shown in other species 35,36 and in mice, 37,38 metamizole is a potent analgesic and can reduce the required dose of other anaesthetics when administered in combination. The doses of butorphanol and metamizole were chosen in accordance with Erhardt et al 7 With the exception of the SKM þ metamizole group, the PWR was lost in all groups with additional administration of analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Our behavioral results are in agreement with research by Nassini et al [ 31 ] and Ince et al [ 28 ], who found that metamizole not only prevents pain induced by scalpel incision in the rat paw but also diminishes tactile hypersensitivity in inflammatory (formalin, carrageenan) and neuropathic (partial sciatic nerve ligation) pain models. Moreover, it has already been shown that metamizole reduces hypersensitivity in neuropathy induced by diabetes [ 32 ] and cancer [ 33 ]. Here, for the first time, we showed that metamizole influences several immunological pronociceptive factors in DRG.…”
Section: Discussionmentioning
confidence: 99%